Comparison of generic drug prices in Korea and eight high-income countries across four therapeutic classes - Chanmi Park; Dong-Sook Kim; Inmyung Song (PLoS ONE, 2025)
Background The prices of generic drugs in general are known to be higher in Korea than in other countries. However, it remains unknown whether the price levels of generic drugs in Korea relative to other countries can differ by therapeutic class. Therefore, this study compared the prices of generic drugs in four commonly used drug classes in Korea with those in other high-income countries. Methods Using IQVIA’s Pricing Insight data from 2018 to 2022, we calculated the Laspeyres price index for generic drugs in four therapeutic classes (antidiabetic drugs, lipid-modifying agents, antihypertensive drugs, and antibiotics). We selected eight high-income countries, such as Canada, France, Germany, Italy, Japan, Switzerland, the United Kingdom, and the United States, for comparison and Korea as the base country. Price to chemist was used and the currency conversion was based on the exchange rate and the purchasing power parity. Results Prices of generic drugs are lower in all of comparison countries combined than in Korea for lipid-modifying drugs and antihypertensive drugs. For these two drug classes, all countries but the U.S. have the index lower than one. The index for antidiabetic drugs was less than one in all countries except for Canada and the U.S. For antibiotics, all countries but France, Italy, and Japan have the index that is greater than one. Furthermore, the price index for generic antibiotics increased from 2018 to 2022 in all countries but Canada and Japan. Conclusion The prices of generic drugs are higher in Korea than in other high-income countries for lipid-modifying agents and antihypertensive drugs. The prices of generic antibiotics are higher in many comparison countries and have further increased from 2018 to 2021.